Exploring a Multi‐modal Experimental Approach to Investigation of Local Embedment Behaviour of Wood under Steel Dowels. (27th September 2016) - Lederer, W.; Bader, T. K.; Muszyński, L.; Eberhardsteiner, J.
Abstract: A multi‐modal experimental approach for analysing the embedment behaviour of timber connections with steel dowels is proposed in this study. In this approach, a standard mechanical embedment test on single‐dowel connections is combined with an optical measurement of surface deformations of the connection based on digital image correlation principle and an X‐ray micro‐computed tomography examination of the deformations in the dowel‐wood interface. The latter is conducted on cylindrical cores including the dowel hole, physically extracted from the loaded specimen at three characteristic points of the load‐deformation curves. The major challenge of this procedure is disrupted load transfer between the cylindrical core specimens and the external material they were plugged in for further analysis. Despite its challenges and limitations, the method revealed a potential for an unprecedented insight into the micromechanics of dowel connections and for effective correlation of the micro‐level observations with the external macroscopic load‐deformation characteristics.